2012
DOI: 10.1103/physreve.86.061502
|View full text |Cite
|
Sign up to set email alerts
|

Finite-size scaling for the glass transition: The role of a static length scale

Abstract: Over the last decade computer simulations have had an increasing role in shedding light on difficult statistical physical phenomena and in particular on the ubiquitous problem of the glass transition. Here in a wide variety of materials the viscosity of a super-cooled liquid increases by many orders of magnitude upon decreasing the temperature over a modest range. A natural concern in these computer simulation is the very small size of the simulated systems compared to experimental ones, raising the issue of h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 39 publications
4
28
0
2
Order By: Relevance
“…140,[152][153][154][155] The size of the system under study can be tuned and finite-size scaling analysis can reveal important lengthscales for the glass problem. 156,157…”
Section: Computer Simulations Of Glass-forming Liquidsmentioning
confidence: 99%
“…140,[152][153][154][155] The size of the system under study can be tuned and finite-size scaling analysis can reveal important lengthscales for the glass problem. 156,157…”
Section: Computer Simulations Of Glass-forming Liquidsmentioning
confidence: 99%
“…[29], it was shown that the length scale obtained via the methods mentioned above for three dimensional systems completely explains the finite size effects seen in the relaxation time τ α for all temperatures including high temperatures. So, for the two dimensional systems, we employed the method of finite-size scaling of τ α [30] to obtain the static length scales as the eigenvalue method and PTS methods involve much larger computational efforts to obtain the length scale. In Fig.1, we have shown the finite-size scaling of τ α to obtain the static length scale for both the two dimensional models.…”
Section: Configurational Entropymentioning
confidence: 99%
“…[22] and employed further in [23]. The starting point of the second method is the fact that at low frequency the tail of the density of state (DOS) of amorphous solids consisting of N particles reflects the excess of plastic modes which do not exist in the density of states of purely elastic solid [24,25].…”
mentioning
confidence: 99%